2019
DOI: 10.1186/s12885-019-5433-7
|View full text |Cite
|
Sign up to set email alerts
|

LUADpp: an effective prediction model on prognosis of lung adenocarcinomas based on somatic mutational features

Abstract: BackgroundLung adenocarcinoma is the most common type of lung cancers. Whole-genome sequencing studies disclosed the genomic landscape of lung adenocarcinomas. however, it remains unclear if the genetic alternations could guide prognosis prediction. Effective genetic markers and their based prediction models are also at a lack for prognosis evaluation.MethodsWe obtained the somatic mutation data and clinical data for 371 lung adenocarcinoma cases from The Cancer Genome Atlas. The cases were classified into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…It was noted that all the 52 genes with most significant difference showed higher mutation rates in the good prognosis group of TCGA cases stratified by the median survival time (Figure 2A). It was consistent with previous findings in lung adenocarcinomas (Yu et al, 2019). Recently, a study identified the association between higher MUC16 gene mutation rate and better prognosis of STADs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was noted that all the 52 genes with most significant difference showed higher mutation rates in the good prognosis group of TCGA cases stratified by the median survival time (Figure 2A). It was consistent with previous findings in lung adenocarcinomas (Yu et al, 2019). Recently, a study identified the association between higher MUC16 gene mutation rate and better prognosis of STADs.…”
Section: Discussionsupporting
confidence: 92%
“…For a variety of tumors, prognosis has been reported to be associated with somatic gene mutations ( Loi et al, 2013 ; Lee et al, 2017 ; Zhang et al, 2017 ; Cho et al, 2018 ; Yu et al, 2019 ). Despite the large heterogeneity of STADs, common genetic factors (e.g., BRCA2 and MUC16) were still identified and reported to be associated with the prognosis ( Chen et al, 2015 ; Li et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To increase the accuracy of predictions in prognosis, data on mutations have been integrated with those of gene expression [ 91 , 92 , 93 ]. However, it is difficult to train an expert system to consider the mutation load of a sample since the effect of a mutation depends on the function of the gene and its position along the gene [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there has been increasing development and integration of novel computational omics methods into the IO clinical arena, particularly pertaining to artificial intelligence (AI). Machine learning (ML) is an AI tool that can process enormous amounts of imported data, enabling classification with predictive capabilities, as it has been shown to predict genotypes associated with poor prognosis 150 . AI may be applied to cellular phenotype detection and classification to determine the presence of a particular disease or its outcome.…”
Section: Novel Ici Approaches To Precision Oncologymentioning
confidence: 99%